The breeding work on development of the spring barley varieties adapted to the non-blackearth region of the Russian Federation and the prospects for growing of the variety in the Ryazan Region - О. V. Levakova (Зерновое хозяйство России)
There has been conducted a comparative analysis of productivity and adaptive potential of 12 spring barley varieties. The field trials of the spring barley varieties were laid in 2009–2019 in crop rotations of the Institute of Seed production and Agrotechnologies, Branch of the Federal Budgetary Scientific Institution “Federal Research Agro-Engineering Center VIM”. The purpose of the study was to conduct research to estimate the role of the variety and variety changing in increasing productivity, to study the dynamics of productivity changes in the breeding process. The trial results identified that the spring barley varieties developed in recent years had an advantage in productivity in comparison with previous ones. The minimum productivity of the new varieties has raised by 22%, which indicates the high efficiency of breeding work on the varieties to improve stress resistance. It was determined that the productivity was on 20–50% higher in the varieties of the new generation. The most productive varieties are ‘Yaromir’ and ‘Znatny’ with 7.1 and 7.48 t/ha, respectively. It has been found that the present varieties in the Ryazan region reveal only 74–78% of their productivity potential, and 85% by the new variety ‘Rafael’. The new varieties have a 10–20% less variation in productivity from year to year, which indicates a high degree of adaptability of the varieties to environmental conditions. There have been presented the promising varieties with high genetic flexibility and stress resistance, a high indicator of productivity stability. It has been established that the varieties ‘Elf’, ‘Nur’, ‘Vladimir’, ‘Yaromir’, ‘Nadezhny’, ‘Znatny’ and ‘Rafael’ have the highest potential of productivity. In terms of stress resistance and stability of productivity, there have been identified the new varieties ‘Znatny’ and ‘Rafael’, developed in recent years.